Sedimentological study of the coastal deposits in the southern part of AL- Badrosiyah coast -Lattakia (Latakia University Journal -Basic Sciences Series, 2023)
Studying the histological characteristics of coastal sediments is of great importance in understanding the mechanism of sediment transport and the effect of transport processes on the shape and size of sediments. In this study, 29 sediment samples were collected from the southern part of the beach of Al-Badrosiyah area during the summer of 2022 in order to determine the nature and distribution of sediments. Whereas, the triangular plots showed the presence of four sedimentary patterns: Gravel, Sandy Gravel, Gravely Sand, and Slightly Gravely Sand, and these data confirm that sedimentation occurred in a high-energy medium with continuous mixing of sediments, while the LDF results showed that the samples was deposited in shallow coastal and marine environments.